Garra findolabium, a new species of cyprinid fish (Teleostei: Cypriniformes) from the Red River drainage in Yunnan, China - Li, Feng-Lian; Zhou, Wei; Fu, Qiang (Zootaxa, 2008)
Garra findolabium, new species, is described from the Red River (Yuan-Jiang in Chinese, Song Hong in Vietnamese) in Yunnan, China. It can be distinguished from all other congeners in Southeast Asia and China by the following combination of characters: posterior edge of the oral sucking disc with a median fissure and divided it into two lamellas; caudal fin with an anomalistic dark patch, extending to 50% of length of caudal fin; no barbels; absence of proboscis in front of nostrils; 37–38 lateral-line scales; 16 circumpeduncular scales; distance of anus to anal-fin origin about 33.3–38.7% of distance of pelvic-fin origin to anal-fin origin.